The making of Donald Trump - Johnston, David Cay 1948- (Melville House, 2016)
Love him or hate him, Trump's influence is undeniable. A man of great media savvy, entrepreneurial spirit, and political clout, Trump's career has been plagued by legal troubles and mounting controversy. Johnston tells the full story of how a boy from a quiet section of Queens, NY would become an entirely new, and complex, breed of public figure. Drawing on decades of interviews, financial records, court documents, and public statements, Johnston gives us the most in-depth look yet at the man who would be president